The Domino's boogergate incident - Crandall, William, 1956- (SAGE knowledge. Cases., 2016)
In April 2009, two Domino's Pizza employees posted a video on YouTube showing one of the employees sticking cheese up his nose and then putting it in a sandwich. This case describes how Domino's handled the public relations crisis.